2011
DOI: 10.1590/s1679-45082011ao1838
|View full text |Cite
|
Sign up to set email alerts
|

Immunological induction with thymoglobulin: reduction in the number of doses in renal transplant from deceased donor

Abstract: Objective:To compare three different regimens of thymoglobulin induction. Methods: One hundred seventy two patients submitted to renal transplantation from a dead donor were divided into three groups according to the total number of thymoglobulin doses used in the post-transplantation surgery: Group 1, until 14 doses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In patients receiving prophylaxis (5 studies), reported rates of CMV infection during the first year post‐SOT were 5.2%, 30 26.0%, 24 45.4%, 31 50.0%, 22 and 50.2% 32 . According to studies conducted in Brazil, India, and South Korea, infection typically appeared after a median of 1–2 months postkidney or postliver transplantation 8,21,25,27,29,32–39 . The diagnostic criteria used for ascertaining CMV infection were similar across studies—whereby a patient was considered to have CMV infection through a positive PCR and/or pp65‐antigenemia assay for CMV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients receiving prophylaxis (5 studies), reported rates of CMV infection during the first year post‐SOT were 5.2%, 30 26.0%, 24 45.4%, 31 50.0%, 22 and 50.2% 32 . According to studies conducted in Brazil, India, and South Korea, infection typically appeared after a median of 1–2 months postkidney or postliver transplantation 8,21,25,27,29,32–39 . The diagnostic criteria used for ascertaining CMV infection were similar across studies—whereby a patient was considered to have CMV infection through a positive PCR and/or pp65‐antigenemia assay for CMV.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic criteria used for ascertaining CMV infection were similar across studies—whereby a patient was considered to have CMV infection through a positive PCR and/or pp65‐antigenemia assay for CMV. However, specimens used for these analyses varied extensively, consisting of either whole blood, plasma, serum, or body fluid, collected periodically during CMV monitoring (frequency and duration of monitoring were not reported) 21–22,24–26,28–35,37,40,41 . In addition, thresholds used to determine whether a patient was positive on the quantitative PCR assay were heterogeneous—such as ≥500 copies/mL (South Korea), 31 ≥1000 copies/mL (India), 24 or >2.500 international units (Brazil) 8,41 .…”
Section: Resultsmentioning
confidence: 99%